Paint roses and castles: traditional narrow boat ainting for homes and boats - Young, Anne (David & Charles, 1992)
The brilliant colours and traditional designs of "roses and castles", the art of the narrow boat painters of the past, can transform mundane household objects into attractive pieces of art. This book explains the techniques for creating items for use in the home - or afloat. It covers topics from creating a good base to adding the finishing touches, and demonstrates how to paint the roses, daisies, leaves, filler strokes, castle scenes and many more patterns which adorned the working boats of days gone by. A wide variety of household objects, including scales, jugs and rusty irons, can be given a new lease of life, and the author has included projects and gift ideas, such as mirror and picture frames, casters, paperweights and pots, all of which can be given a personalized touch. The book also contains a list of useful addresses and places of interest.